Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Given a triangle $\Delta ABC$ with circumcenter $O$, and incenter $I$.

If $∠ABC = 45°$, $OI = d$, and $c − b = d√2$,

Find the value of $\sin A$.

I've thought of using the fact that $d^2 = R(R-2r)$ where $R$ is the circumradius and $r$ is the inradius. But I didn't know where to apply it.

share|improve this question
2  
"Find the possible value of $\sin A$." makes no sense. Do you mean "Find the possible values of $\sin A$." or "Find the value of $\sin A$."? –  joriki Dec 21 '12 at 17:11

2 Answers 2

Seat your belt, it will be great...

You can use your $d^2 = R(R-2r)$, which gives you

$(c-b)^2 = 2d^2 = 2R(R-2r) = 2R^2-4rR$

Then, you remark that the area of the triangle can be obtained with $r$ or with $R$ :

$\displaystyle\text{Area} = \frac{(a+b+c)r}{2}$ and $\displaystyle\text{Area} = \frac{ab\sin{C}}{2} = \frac{abc}{4R}$

So you have $\displaystyle\frac{(a+b+c)r}{2} = \frac{abc}{4R}$, thus $\displaystyle2rR=\frac{abc}{a+b+c}$

Putting it in the first equality gives :

$\displaystyle c^2+b^2-2bc = 2R^2-2\frac{abc}{a+b+c}$

But $\displaystyle \frac{b}{\sin{B}} = 2R$ and $\displaystyle\sin{B} = \frac{\sqrt{2}}{2}$, so $b=\sqrt{2}R$ and

$\displaystyle c^2+b^2-2bc = b^2-2\frac{abc}{a+b+c}$

$\displaystyle\Leftrightarrow c^2 - 2bc = -2\frac{abc}{a+b+c}$

$\displaystyle\Leftrightarrow c - 2b = -2\frac{ab}{a+b+c}$

$\displaystyle\Leftrightarrow (c - 2b)(a+b+c) = -2ab$

$\displaystyle\Leftrightarrow ac+bc+c^2-2ab-2b^2-2bc = -2ab$

$\displaystyle\Leftrightarrow ac+c^2-2b^2-bc = 0$

Now, we can use $a = 2R\sin A$, $b = 2R\sin B$, and $c = 2R\sin C$ to

$\displaystyle \sin A \sin C+\sin^2 C-2\sin^2 B-\sin B \sin C = 0$

$\displaystyle\Leftrightarrow \sin A \sin C+\sin^2 C-1-\frac{\sqrt{2}}{2} \sin C = 0$

We also know that

$\sin C = \sin(180°-45°-A) = \sin 135° \cos A - \sin A \cos 135° = \frac{\sqrt{2}}{2}(\cos A + \sin A)$

Thus,

$\displaystyle \sin A \frac{\sqrt{2}}{2}(\cos A + \sin A)+\frac{1}{2}(\cos A + \sin A)^2-1- \frac{1}{2}(\cos A + \sin A) = 0$

$\displaystyle\Leftrightarrow \sqrt{2} \sin A \cos A + \sqrt{2}\sin^2 A+\cos^2 A + \sin^2 A + 2\sin A \cos A-2- \cos A - \sin A = 0$

$\displaystyle\Leftrightarrow (2+\sqrt{2}) \sin A \cos A + \sqrt{2}\sin^2 A -1 - \cos A - \sin A = 0$

To only have $\sin$, we can isolate $\cos A$ and square terms...

$\sqrt{2}\sin^2 A - \sin A - 1 = \cos A (1 - (2+\sqrt{2}) \sin A)$

$\Rightarrow (\sqrt{2}\sin^2A - \sin A - 1)^2 = \cos^2 A (1 - (2+\sqrt{2}) \sin A))^2$

Let $x = \sin A$ :

$(\sqrt{2}x^2-x-1)^2 = (1-x^2)(1 - (2+\sqrt{2}) x)^2$

$\Leftrightarrow 2x^4+x^2+1-2\sqrt{2}x^3-2\sqrt{2}x^2+2x = (1-x^2)(1 - (4+2\sqrt{2})x + (6+4\sqrt{2})x^2)$

$\Leftrightarrow 2x^4-2\sqrt{2}x^3+(1-2\sqrt{2})x^2+2x+1 = -(6+4\sqrt{2}) x^4 + (4+2\sqrt{2})x^3+(5+4\sqrt{2})x^2 - (4+2\sqrt{2})x + 1$

$\Leftrightarrow (8+4\sqrt{2})x^4-(4+4\sqrt{2})x^3-(4+6\sqrt{2})x^2+(6+2\sqrt{2})x = 0$

A solution is $x = 0$ which is impossible so it gives us :

$(4+2\sqrt{2})x^3-(2+2\sqrt{2})x^2-(2+3\sqrt{2})x+(3+\sqrt{2}) = 0$

Aaaand... I don't want to find the solution, especially since I've probably make a mistake somewhere :D. There surely is something shorter but perhaps It could help you to find a nice solution!

share|improve this answer

keep going:$\ (4+2\sqrt{2})x^3-(2+2\sqrt{2})x^2-(2+3\sqrt{2})x+(3+\sqrt{2})=4x^3-2\sqrt{2}x^2+2\sqrt{2}x^3-2x^2-3\sqrt{2}x+3-2x+\sqrt{2}=2\sqrt{2}x^2*(\sqrt{2}x-1)+2x^2(\sqrt{2}x-1)-3(\sqrt{2}x-1)-(\sqrt{2})(\sqrt{2}x-1)=(\sqrt{2}x-1)[(2\sqrt{2}+2)x^2-(3+\sqrt{2})]$=0

$\ x=\sqrt{2}/2$ or $\ x^2=(3+\sqrt{2})/(2\sqrt{2}+2)$ ie $\ x=\sqrt{(2\sqrt{2}-1)/2} $

now you can know $\sin A$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.